Ketika Tuhan mempercayakan anak berkebutuhan khusus: Dinamika psikologis dan spiritualitas orangtua - Aprianus Simanungkalit (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2026)
The birth of a child with special needs confronts parents with distinct psychological and spiritual dynamics, from initial shock, denial, and guilt toward an acceptance achieved through prolonged adaptation. Prior studies have generally examined the psychological and spiritual dimensions separately, leaving their interaction, particularly from a Christian spirituality perspective, underexplored. This study analyzes the psychological dynamics parents experience in raising a child with special needs, the role of spirituality in caregiving adaptation, and their interaction in shaping parental resilience. The study used a descriptive qualitative method with a theological-biblical approach, combining analysis of Scripture and family-psychology literature with in-depth interviews involving four parent and educator informants. Findings showed that early responses of shock, denial, and guilt gradually gave way to acceptance as parents internalized Christian spirituality as religious coping, reframing the child's presence as a gift and evidence of God's providence. This interaction between psychological well-being and spiritual maturity shapes parental resilience, underscoring the need for pastoral sensitivity and inclusive church ministry for such families. These findings provide a basis for developing parenting-support programs, Christian counseling, and pastoral care more responsive to their psychological and spiritual needs.